ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN DAN PENGARUHNYA TERHADAP HARGA SAHAM PERUSAHAAN - Yunita Kristina Petingko; Agus Surata; Heni Handri Utami (Jurnal Dinamika Sosial Ekonomi, 2015)
This study aims to determine the financial performance of plantation companies which shares are listed in Indonesia Stock Exchange and also to determine the effect on the financial performance of the company's stock price in the plantation subsector which listed in Indonesia Stock Exchange (IDX). The basic method used descriptive analysis method. Methods of the execution using empirical studies and methods of determining the location used purposive. The kinds of data as per requested is secondary data. Source of data obtained from IDX and annual financial statements plantation companies listed in Indonesia Stock Exchange. Data collection techniques by means of literature and interviews. To determine the financial performance of companies use financial ratio analysis, to determine the effect of the financial performance of the stock price used multiple linear regression analysis. The results showed that the company's financial performance deteriorated Go Public plantation during the period of  analysis and trend declining financial performance. Impairment of financial ratios resulted in a decrease in the company's stock price due to significant financial performance as measured from thirteen financial ratios used as independent  variables in this study had an influence on the company's stock price and from the thirteenth to the financial ratios, which have a significant positive effect on stock prices is the total asset turnover ratio and ROA. Keywords: Plantation Company, Financial Performance, Financial Ratio, Stock Price